Representations of Family Dynamics in the Plays the Burdens and The Play Black Mamba by John Ruganda. - Amutuhaire, Linet (Kabale University, 2024)
The study focused on the representation of family dynamics in John Ruganda's plays The Burdens and Black Mamba. It aimed to examine how family relationships and dynamics are portrayed, investigate the socio-economic factors influencing these dynamics, and assess the impact of family dynamics on the characters' well-being. The research involved a critical and thorough internalization of the plays, careful reading of relevant literature, and the use of authentic journals and articles, accurately relating them to the topic. A close analysis approach was adopted to systematically analyze information, leading to useful recommendations and conclusions about family dynamics. The Burdens and Black Mamba were the primary research instruments, supplemented by documentary guides. Data was analyzed through descriptive and textual analysis, confirming that family dynamics are represented through various characters in the plays. The research highlighted the crucial role of family in the lives of individuals in any community. These plays offer valuable insights into the interplay between socio-economic factors, familial relationships, and individual well-being, shedding light on the challenges of family life in the modern world. These findings are discussed in the subsequent chapters of the research report.